2021
DOI: 10.3390/ijerph18062846
|View full text |Cite
|
Sign up to set email alerts
|

Accentuating the Interrelation between Consumer Intention and Healthy Packaged Food Selection during COVID-19: A Case Study of Pakistan

Abstract: This study contemplates the factors that influence consumer intention, before and during the eruption of COVID-19, for the selection of healthy packaged food in Pakistan. The extant studies have identified two distinct attitudes of consumers about food label information: one is its usefulness and the second elucidates the avoidance. Hence forth, the current study contributes to the extant literature while signifying both reasons which motivate consumers to read food labels and reasons which discourage consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The most used online platforms during the COVID-19 pandemic were Google Meetings and Zoom. Moreover, previous studies revealed that the demand for video conferencing apps has surged during the TW [97] and the most used online educational platforms were Microsoft Teams and Zoom [98].…”
Section: Discussionmentioning
confidence: 99%
“…The most used online platforms during the COVID-19 pandemic were Google Meetings and Zoom. Moreover, previous studies revealed that the demand for video conferencing apps has surged during the TW [97] and the most used online educational platforms were Microsoft Teams and Zoom [98].…”
Section: Discussionmentioning
confidence: 99%
“…This situation may have increased the interest in foods, and therefore, the food label reading rates may have increased. Moreover, one study showed that during the COVID-19 period, consumers turned to packaged foods with label information due to food safety (Zafar et al, 2021). Therefore, it would be reasonable to think that consumers with food safety concerns are more likely to read food labels.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with the studies by Bennet et al [102] and Di Renzo et al [103], which highlighted that people had positive changes in eating habits due to the pandemic, improving eating behavior by increasing the intake of healthier food and decreasing their consumption of junk food. Furthermore, Zafar et al [104] concluded that during the COVID-19 pandemic, consumers have chosen to consult nutritional labels more, choosing foods that contribute to their health.…”
Section: Discussionmentioning
confidence: 99%